Coraliomargarita parva sp. nov., isolated from mangrove sediment and genome-based analysis of the class Opitutae revealed five novel families: Coraliomargaritaceae fam. nov., Pelagicoccaceae fam. nov., Cerasicoccaeae fam. nov., Oceanipulchritudinaceae fam. nov., and Alterococcaeae fam. nov. - Min, Lingli; Wang, Wenzhuo; Oren, Aharon; Lai, Qiliang; Huang, Zhaobin (Frontiers in Microbiology, 2023)
Members of the class Opitutae are widely distributed in various environments such as rice paddy soil, freshwater lakes, seawater, marine sediment, and invertebrate digestive tracts. The class currently consists of two orders, Opitutales and Puniceicoccales, represented by the families Opitutaceae and Puniceicoccaceae, respectively, which are primarily delineated on the basis of 16S rRNA gene sequences and limited phenotypic characterizations of a few type strains. The scarcity of 16S rRNA gene and genome sequences generated from the type strains of the class Opitutae constrained our understanding of the ecological distribution and adequate resolution of its taxonomy. Here, an Opitutae strain designated WMMB3T, isolated from a mangrove sediment, was subjected to taxonomic characterization. The 16S rRNA gene of strain WMMB3T shared high sequence similarities with Coraliomargarita akajimensis DSM 45221T and C. sinensis WN38T of 96.1 and 95.9%, respectively. Phylogenetic analysis suggested that strain WMMB3T formed a monophyletic branch affiliated to the genus Coraliomargarita. The average nucleotide identity (ANI) values, digital DNA–DNA hybridization (dDDH) values and average amino acid identity (AAI) values of strain WMMB3T compared between Coraliomargarita members were 71.8–72.5, 20.7, and 68.2–68.7%, respectively, indicating that strain WMMB3T represented a novel species of Coraliomargarita. The genome of strain WMMB3T was 4.5 Mbp with a DNA G + C content of 56.0%. The respiratory quinone was menaquinone-7. The major fatty acids were iso-C14:0, and C18:1ω9c. Based on genomic, phenotypic, and chemotaxonomic characterizations, strain WMMB3T represents a novel species, and Coraliomargarita parva sp. nov. is proposed. Additionally, the phylogenomic analysis of more than 500 genomes of the class Opitutae, encompassing a majority of uncultivated bacteria and a few type strains, was performed using the Genome Taxonomic Database toolkit (GTDB-Tk) to present adequate resolution of the taxonomy. Combined with 16S rRNA gene sequence phylogeny and genomic relatedness, five novel families retrieved mainly from marine habitats were proposed: Coraliomargaritaceae fam. nov., Pelagicoccaceae fam. nov., Cerasicoccaeae fam. nov., Oceanipulchritudinaceae fam. nov., and Alterococcaeae fam. nov. AAI values of 58–60% could be considered as the boundary to delineate families of the class Opitutae. This study provided a new taxonomic framework of the class Opitutae based on the genomic data.